Spatial Mapping Analysis of Stunting Incidents in Bireuen District - Nuraina Nuraina; Cut Azizah; Siti Rahmah (GLOBAL HEALTH SCIENCE GROUP, 2023)
The prevalence of stunting in Indonesia still really needs attention from all sectors, even though there has been a decline in the last decade, the figure is in the highest category among countries in Southeast Asia. Objective: This research was conducted with the aim of analyzing the spatial distribution of stunting incidents in Bireuen Regency. Method: This research is an analytical descriptive observational study with an ecological study design and using a spatial epidemiology approach. Researchers use Geographic Information Systems (GIS) and spatial analysis based on secondary data. Spatial analysis in this study was used to determine the distribution pattern of stunting and spatial correlation with the incidence of stunting in Bireuen Regency. Results: Based on spatial mapping analysis carried out in the Regency, it was found that the highest prevalence of stunting occurred in 2022, showed that the prevalence of stunting is in the very high category (in red), namely there are 3 villages with a percentage (>40%) spread across Jeumpa and Peusangan Regencies (figure 7). However, the largest number of locus villages were found in 2023 with a total of 50 villages (figure 5). Conclusions: Based on spatial analysis, the results showed that the prevalence of stunting from 2021-2023 was very high in 2022, namely there were 3 villages with a percentage (>40%) spread across Jeumpa and Peusangan Districts. However, the largest number of locus villages were found in 2023 with 50 villages. The Bireuen Regency Government continues to strive to prevent stunting so that the next generation in Bireuen Regency becomes a smart and high-quality generation capable of competing globally.